Mechanical Engineering, Materials Science and Civil Engineering selected, peer reviewed papers from the 2014 - (Zheng) Li, Jeremy (Applied mechanics and materials, 2015)
Collection of selected, peer reviewed papers from the 2014 the 3rd International Conference on Mechanical Engineering, Materials Science and Civil Engineering (ICMEMSCE2014), October 25-26, 2014, Phuket, Thailand